On the problem of HIV infection in the objects of forensic medical expertise - Ivanov, P L; Timoshenko, T V; Zemskova, E Yu (Sudebno-meditsinskaia ekspertiza, 2017)
The authors overview the current state of research in the field of diagnostics and identification of the signs suggesting the presence of HIV in the materials obtained from the human corpses undergoing forensic medical expertise at different stages of their post-mortem changes. Another objective of the present work was to evaluate the risk of HIV infection for the medical personnel involved in the autopsy studies taking into consideration the significance attached in different countries to the problem of anti-infectious protection of the staff of the state institutions of forensic medical expertise. The authors discuss the possibilities and limitations of the application of the methods for HIV diagnostics, such as immunoenzymatic assays. The special attention is given to the advantages of the molecular genetic methods based on the use of the specific fragments of the viral RNA genome as the diagnostic markers. The solid methodological basis for molecular genetic diagnostics of HIV infection is provided by PCR-amplification with the detection in the real-time regime. It is supposed that this approach will make it possible not only to determine, with the high degree of accuracy and specificity, the presence of the viral genome in the biological materials but also to reduce to a minimum the probability of both false-positive and false-negative responses.